2019
DOI: 10.1002/adma.201807008
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Topological Hall Effect in a SrRuO3 Single Layer

Abstract: Topological Hall effect (THE), appearing as bumps and/or dips in the Hall resistance curves, is considered as a hallmark of the skyrmion spin texture originated from the inversion symmetry breaking and spin–orbit interaction. Recently, Néel‐type skyrmion is proposed based on the observed THE in 5d transition metal oxides heterostructures such as SrRuO3/SrIrO3 bilayers, where the interfacial Dzyaloshinskii–Moriya interaction (DMI), due to the strong spin–orbit coupling (SOC) in SrIrO3 and the broken inversion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 21 publications
9
137
0
Order By: Relevance
“…Tetragonal structure was reported also for epitaxial SRO films grown on orthorhombic GdScO 3 (110) and NdGaO 3 (110) substrates [19,26], on GdScO 3 -buffered SrTiO 3 (100) [27] and for oxygen-deficient epitaxial SRO films grown on SrTiO 3 (100) [28].…”
Section: Structural Characterizationmentioning
confidence: 68%
“…Tetragonal structure was reported also for epitaxial SRO films grown on orthorhombic GdScO 3 (110) and NdGaO 3 (110) substrates [19,26], on GdScO 3 -buffered SrTiO 3 (100) [27] and for oxygen-deficient epitaxial SRO films grown on SrTiO 3 (100) [28].…”
Section: Structural Characterizationmentioning
confidence: 68%
“…[ 38,48 ] In the authors' previous work, they had effectively modulated oxygen octahedral rotation via oxygen engineering, which gave rise to THE in SRO layer with a thickness of 3–6 nm. [ 15 ] Based on these reasons, they introduced a weak bulk DMI constant D = 3.8 × 10 −4 J m −2 for SRO in their simulations.…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] Moreover, oxygen octahedral rotation/tilting [ 13 ] and microstructural defects [ 14 ] are demonstrated as additional origins of the DMI. Our previous work [ 15 ] found the emergence of THE in SRO single layer with a thickness of 7–15 unit cells through the modulation of RuO 6 oxygen octahedra via oxygen engineering. Considering that microstructural defects in the sample are uncontrollable, we propose a new approach to stabilize magnetic topological states by antiferromagnetic order.…”
Section: Figurementioning
confidence: 99%
“…The authors attributed the modulation to the variation of the spin-orbit coupling at the interface of SrRuO3 and SrIrO3 and emphasized the importance of nonmagnetic interlayer SrIrO3 that has large spin-orbit coupling in this work. and c +200 V. [48] Most recently, Qin et al [49] realized the electric-field control of topological Hall effect in a single SrRuO3 layer and they applied electric fields by ionic liquid (Fig. 15a).…”
Section: Electric-field Control Of Noncollinear Spin Structurementioning
confidence: 99%
“…In this work, the electric potential gradient in the surface of SrRuO3 tunes the spin-orbit coupling thus arouse the change of Dzyaloshinskii-Moriya interaction rather than magnetic exchange energy or the anisotropy energy of the single SrRuO3 layer. [ 49] On the other side, in multiferroic MnWO4, Finger et al [50] demonstrated that the switch of the chiral component by applied electric fields. As given in Fig.16a-d, after cycling the voltage, the chiral radio can always return to the initial value.…”
Section: Electric-field Control Of Noncollinear Spin Structurementioning
confidence: 99%